NLRP3 Influences Cognitive Function in Schizophrenia in Han Chinese - Liu, Ruimei; Tang, Wei; Wang, Weiping; Xu, Feikang; Fan, Weixing; Zhang, Yi; Zhang, Chen (Frontiers in Genetics, 2021)
It has been proposed that immune abnormalities may be implicated with pathophysiology of schizophrenia. The nod-like receptor pyrin domain-contraining protein 3 (NLRP3) can trigger immune-inflammatory cascade reactions. In this study, we intended to identify the role of gene encoding NLRP3 (NLRP3) in susceptibility to schizophrenia and its clinical features. For the NLRP3 mRNA expression analysis, 53 drug-naïve patients with first-episode schizophrenia and 56 healthy controls were enrolled. For the genetic study, a total of 823 schizophrenia patients and 859 controls were recruited. Among them, 239 drug-naïve patients with first-episode schizophrenia were enrolled for clinical evaluation. There is no significant difference in NLRP3 mRNA levels between patients with schizophrenia and healthy controls (P=0.07). We did not observe any significant differences in allele and genotype frequencies of rs10754558 polymorphism between the schizophrenia and control groups. We noticed significant differences in the scores of RBANS attention and total scores between the patients with different genotypes of rs10754558 polymorphism (P=0.001 and P<0.01, respectively). Further eQTL analysis presented a significant association between the rs10754558 polymorphism and NLRP3 in frontal cortex (P=0.0028, P=0.028 after Bonferroni correction). Although our findings did not support NLRP3 confer susceptibility to schizophrenia, NLRP3 may be a risk factor for cognitive impairment, especially attention deficit in this disorder.